2005
DOI: 10.1677/erc.1.00857
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of endocrine resistance and novel therapeutic strategies in breast cancer

Abstract: Tamoxifen has been the mainstay of hormonal therapy in both early and advanced breast cancer patients for approximately three decades. The availability of novel compounds such as aromatase inhibitors (AIs) and fulvestrant, with different mechanism of action, is changing the scenario of endocrine treatment of postmenopausal breast cancer patients. In this review article, we have summarized the current knowledge of the mechanisms of resistance to endocrine therapy, in order to derive information that might be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
225
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(236 citation statements)
references
References 138 publications
(128 reference statements)
3
225
0
8
Order By: Relevance
“…Current literature supports the hypothesis that acquired resistance is mainly mediated by molecular events that-particularly in the case of resistance to AIs-lead to constitutive activation of ERa and growth factor signaling pathway cross-talk (Clarke et al, 2003;Martin et al, 2003;Yue et al, 2003;Jelovac et al, 2005;Normanno et al, 2005;Sabnis et al, 2005;Santen et al, 2005;Masri et al, 2008). On the basis of these studies, several clinical trials have attempted to overcome resistance through combination with growth factor signaling inhibitors Massarweh and Schiff, 2006).…”
Section: Introductionmentioning
confidence: 84%
“…Current literature supports the hypothesis that acquired resistance is mainly mediated by molecular events that-particularly in the case of resistance to AIs-lead to constitutive activation of ERa and growth factor signaling pathway cross-talk (Clarke et al, 2003;Martin et al, 2003;Yue et al, 2003;Jelovac et al, 2005;Normanno et al, 2005;Sabnis et al, 2005;Santen et al, 2005;Masri et al, 2008). On the basis of these studies, several clinical trials have attempted to overcome resistance through combination with growth factor signaling inhibitors Massarweh and Schiff, 2006).…”
Section: Introductionmentioning
confidence: 84%
“…It has been demonstrated that several signaling kinases interacted with and were activated by the ER, including IGF-1R (insulin-like growth factor-1 receptor), Src, PI3K (phosphatidylinositol 3-kinase), MAPK (mitogen-activated protein kinase), protein kinases A and C and calcium pathways [65], EGFR (epidermal growth factor receptor) and ErbB-2, with non-genomic effects of the ER [66,67]. Furthermore, genomic and non-genomic mechanisms of action of ER are not mutually exclusive, but many interactions exist between these two modes [4]. …”
Section: Discussionmentioning
confidence: 99%
“…The genomic action mode mediates genomic transcription regulation through nuclear-initiated steroid signaling, and the non-genomic mode activates various protein kinase cascades [4]. Both the genomic and non-genomic pathways play a role in the response to estrogen signaling and are regulated by TFs in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its long term use is limited by life-threatening adverse effects [6][7][8][9] , and some patients can become resistant [10,11] . As a result of these challenges, three AIs including ANA were introduced to either serve as TAM alternatives or to be used following several years of TAM therapy [4,10,[12][13][14] .…”
mentioning
confidence: 99%